Antihelmintic treatment of goats on an arid range and its effect on milk production early in lactation - Mellado, Miguel; González, Henry; Valdéz, Raul; Pastor, Francisco (Ciência Animal Brasileira / Brazilian Animal Science, 2006)
The effect of a single anthelmintic treatment at thebeginning of lactation on milk production and composition, live weight change and blood chemistry in mix-breeds goats was studied in an arid zone of northern Mexico. Ten adult goats were treated with Closantel ® subcutaneously at 8.0mg kg-1 BW. Eleven adult goats were used as untreated controls. The overall total trial reduction in fecal egg counts due to anthelmintic treatment was 96%, but this fecal egg counts reduction did not affect live weight change (-13 ±0.5 and -15 ± 0.3 g d-1 for treated and control does), milk yield(30.7 ± 0.4 and 33.6 ± 0.8 L in 73 days of lactation for treated and control does). No significant differences were seen in milk composition and blood profiles between treated and untreated goats. It was concluded that, in the present context of goat exploitation under traditional extensive village system in an arid environment, parasite burdens at the beginning of lactation were not sufficiently severe to affect milk production and weight change of goats. KEY WORDS: Anthelmintic treatment, blood chemistry, body weight, goats, milk production, gastrointestinal nematodes.